The current landscape of CAR T-cell therapy for solid tumors: Mechanisms, research progress, challenges, and counterstrategies - Daei Sorkhabi, Amin; Mohamed Khosroshahi, Leila; Sarkesh, Aila; Mardi, Amirhossein; Aghebati-Maleki, Ali; Aghebati-Maleki, Leili; Baradaran, Behzad (Frontiers in Immunology, 2023)
The successful outcomes of chimeric antigen receptor (CAR) T-cell therapy in treating hematologic cancers have increased the previously unprecedented excitement to use this innovative approach in treating various forms of human cancers. Although researchers have put a lot of work into maximizing the effectiveness of these cells in the context of solid tumors, few studies have discussed challenges and potential strategies to overcome them. Restricted trafficking and infiltration into the tumor site, hypoxic and immunosuppressive tumor microenvironment (TME), antigen escape and heterogeneity, CAR T-cell exhaustion, and severe life-threatening toxicities are a few of the major obstacles facing CAR T-cells. CAR designs will need to go beyond the traditional architectures in order to get over these limitations and broaden their applicability to a larger range of malignancies. To enhance the safety, effectiveness, and applicability of this treatment modality, researchers are addressing the present challenges with a wide variety of engineering strategies as well as integrating several therapeutic tactics. In this study, we reviewed the antigens that CAR T-cells have been clinically trained to recognize, as well as counterstrategies to overcome the limitations of CAR T-cell therapy, such as recent advances in CAR T-cell engineering and the use of several therapies in combination to optimize their clinical efficacy in solid tumors.